Selection of an autochthonous yeast starter culture for industrial production of Primitivo "Gioia del Colle" PDO/DOC in Apulia (Southern Italy). (January 2019) - Tufariello, M.; Maiorano, G.; Rampino, P.; Spano, G.; Grieco, F.; Perrotta, C.; Capozzi, V.; Grieco, F.
Abstract: The aim of the present study was to isolate and characterize yeast strains as good candidates for driving the industrial fermentation process, from natural must fermentations of "Primitivo" grape cultivar, grown in the PDO/DOC "Gioia del Colle" (Apulia, Southern Italy). The selection protocol was based on parameters such as low production of acetic acid and hydrogen sulphide, complete sugar consumption during fermentation, significant production of some classes of volatile molecules responsible for wine aroma. Three Saccharomyces cerevisiae strains, named ITEM14088, ITEM14090 and ITEM14093, successfully dominated the fermentation process and contributed to increase organoleptic quality of the produced wines. The best performing strain, namely ITEM14093, was used as fermentation starter for three different industrial vinifications. The wines obtained were characterized by high levels of esters, associated to fruity nuances, as well as of alcohols responsible for vinous, sweet and floral notes. Furthermore, from a sensory point of view, all wines were positively judged, being characterized by frankness, gustatory persistence and intensity, good balance and body wine. Highlights: Three strains of S. cerevisiae strains from Primitivo grapes were oenologically selected. The strain oenological performances were tested by pilot-scale vinifications. Primitivo wine was produced in three cellars using the ITEM14093 strain. We suggest the need of a local based formulation for autochthonous starter cultures.